HIGH SULFIDATION EPITHERMAL MINERALIZATION AND ORE MINERAL ASSEMBLAGES OF CIJULANG PROSPECT, WEST JAVA, INDONESIA - Myo Min Tun; I Wayan Warmada; Arifudin Idrus; Agung Harijoko; Okki Verdiansyah; Koichiro Watanabe (Journal of Applied Geology, 2015)
Cijulang is a high-sulfidation epithermal system hosted in the calc-alkaline rocks of andesite lava and lapilli tuff. Mineralization in the prospect is characterized by pyrite-enargite-gold and associated acid sulfate alteration. Studies on ore and gangue mineral assemblages and their mutual textural relationships were carried out in order to explore the paragenetic sequence of mineralization. Hypogene mineralization primarily occurs in the silicic core and the advanced argillic zone in the form of massive replacement, fracture-filling veinlets, vug-filling, patches and dissemination. Mineralization is apparently controlled by both lithology and structures. Common ore minerals include pyrite, enargite, luzonite, tennantite, chalcopyrite, covellite, galena, emplectite and Te-bearing minerals. The paragenetic study indicates that the epithermal prospect evolved from an early stage of intense acid leaching resulting in the formation of vuggy silica and advantage argillic mineral assemblage which was followed by the sulfides deposition. Two metal stages were identified during ore deposition: an early Fe-As-S stage and the later Cu-Fe-As-S stage. The former stage is char- acterized high-sulfidation state sulfides such as enargite/ luzonite+covellite whereas a later stage of Cu- Fe-As–S is represented by intermediate sulfidation state sulfides assemblage of tennantite+chalcopyrite. Gold is probably introduced in the early stage within the ore system and more abundant in the late stage. Keywords: Cijulang, high-sulfidation, acid sulfate, mineralization, enargite, paragenetic, metal stages